FWM-based multi-wavelength erbium-doped fiber laser using Bi-EDF - Ahmad, Harith; Parvizi, Roghaieh; Dimyati, Kaharudin; Tamjis, Mohamad Rom; Harun, Sulaiman Wadi (IOP Publishing, 2010)
We experimentally demonstrate a simple structure but efficient multi-wavelength erbium-doped fiber laser (EDFL) using a 49 cm Bismuth-based erbium-doped fiber (Bi-EDF) as gain medium. The Bi-EDF provides erbium amplification and FWM effect in the cavity to generate a stable multi-wavelength comb operating in C-band region. We have achieved more than 5 lines with peak power of more than -35 dBm and channel spacing of 0.5 nm by incorporating a broadband fiber Bragg grating and polarization controller in the ring cavity.